Wiki-Thanks: cultural differences in thanks networks by analysing who thanks whom in different-language Wikipedias. (2016) - Nemoto, Keiichi; Okada, Ken-Ichi
Wikipedia is one of the world's largest social production platforms, featuring high quality articles without a central control. Many scholars have investigated how people in creating articles for the online encyclopaedia collaborate with other authors. Wikipedia is available in 288 languages, among which are Finish, Korean, and Japanese, languages which are not spoken outside of the countries in which they originated. Therefore, Wikipedia offers a type of microscope for analysing how people in these local cultures work together. In May 2013, the English Wikipedia introduced a new social function - Wiki-Thanks. This facility enables authors to send thanks to other Wikipedia users who have contributed to or edited their articles. In this paper, we aim to evaluate this new social tool from different cultural perspectives. To achieve this goal, we analyse Wiki-Thanks log events and compare different language editions of Wikipedia - English, German, Spanish, Chinese, Japanese, Korean, and Finnish.